ISLAM DAN DAKWAH SOSIAL KEMANUSIAAN - Hilmy, Baso (Jurnal Dakwah Tabligh, 2015)
Islam is a proselytizing religion, which always stressed to his followers to always preach in every circumstance. Dawa is amalakan relating to social humanity. The view among the first to place more emphasis on the study of the normative teachings, the two tend to emphasize the need for reorientation of religious understanding at present empirical reality. So, the first party to invite to reflection-normative, the two parties over the actual reflection and empirical.